2020
DOI: 10.1007/s10493-020-00541-y
|View full text |Cite
|
Sign up to set email alerts
|

Management of the poultry red mite, Dermanyssus gallinae, using silica-based acaricides

Abstract: Four silica-based acaricides were examined in laboratory tests for their effectiveness against poultry red mite, Dermanyssus gallinae. All acaricides resulted in 100% mite mortality. Two groups of active ingredients could be differentiated. The products Silicosec® and Ewazid®, based on naturally occurring diatomaceous earth (DE), killed 100% of adult D. gallinae within 48 h exposure time. The time to kill 50% of the mites (LT50) was calculated to be 31.7 and 34.9 h, respectively. The other two products, contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The mite remains inside crevices, in organic materials, protected from contact with the products sprayed in the environment [7,53,102]. Ulrich and Han [103] obtained good mortality results against D. gallinae with products based on diatomaceous earth under laboratory conditions, but did not obtain significant results when using the same products in field tests, which may have been influenced by the physical properties of the products [103], ambient humidity [78], or changes in climate that did not allow the mites to absorb the products [103]. The numbers 1,2 correspond to product, chemical class, and mortality.…”
Section: Diatomaceous Earth and Synthetic Silica-based Productsmentioning
confidence: 99%
“…The mite remains inside crevices, in organic materials, protected from contact with the products sprayed in the environment [7,53,102]. Ulrich and Han [103] obtained good mortality results against D. gallinae with products based on diatomaceous earth under laboratory conditions, but did not obtain significant results when using the same products in field tests, which may have been influenced by the physical properties of the products [103], ambient humidity [78], or changes in climate that did not allow the mites to absorb the products [103]. The numbers 1,2 correspond to product, chemical class, and mortality.…”
Section: Diatomaceous Earth and Synthetic Silica-based Productsmentioning
confidence: 99%
“…DE has many commercial preparations such as Drycide, Insecto ® , Perma Guard, Untreated, Silicosec, and Diafil 610, which are generally used around the world (Athanassiou et al, 2003;Ziaee and Khashaveh, 2007;Wakil et al, 2010;Alagöz and Sağlam, 2022). In studies with the Acarina order, different formulations of diatomaceous earth are generally focused on the families Dermanyssidae (Kilpinen and Steenberg, 2009;Steenberg and Kilpinen, 2014;Kilpinen and Steenberg, 2016;Alves et al, 2019;Alves et al, 2020;Ulrichs et al, 2020), and Macronyssidae (Mullens et al, 2012;Martin and Mullens, 2012;Murillo and Mullens, 2016). There are few studies on the effectiveness of DE on T. urticae (Shah and Appleby, 2019;Başkaya, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, it also increases the number of insect pests and diseases, leading to the heavy use of veterinary drugs during animal husbandry. Husbandry operations employ many different types of veterinary drugs, including organophosphates, carbamates, and pyrethroids, to control poultry red mite infestations and prevent economic losses due to reduced egg production 3 , 4 . In 2007, European authorities reported that eggs and chickens were contaminated with pesticides banned in livestock farming, such as fipronil.…”
Section: Introductionmentioning
confidence: 99%
“…Eggs tainted with insecticides have also been discovered in Korea, which has resulted in major food safety-related issues. Because few veterinary drugs are registered as insecticides in Korea and resistance to approved acaricides is prevalent 4 , 5 , insecticides are often illegally used for cage-grown animals.…”
Section: Introductionmentioning
confidence: 99%